Impact of arabinoxylan-enriched diets on the intestinal chemical barrier and microbiota composition in rainbow trout (Oncorhynchus mykiss) - Zhang, Xindang; Wang, Hengzhi; Lin, Beibei; Meng, Xiaolin; Deng, Junming (Frontiers in Veterinary Science, 2024)
IntroductionThis study was conducted to evaluate the effects of dietary AX inclusion on the chemical barrier, antioxidant function and intestinal microbiome of rainbow trout.MethodsFive isoproteic and isolipidic experimental diets were formulated to contain 0.03% arabinoxylanase, as well as 0%, 2.5%, 5% and 10% AX (CAX, Con, AX2.5, AX5 and AX10), respectively.ResultsThe trypsin and maltase activities in the foregut of AX10 group were significantly lower than those in Con group. Similarly, the amylase and sucrase activities of the middle intestinal mucosa, maltase of the distal intestinal mucosa, and MUC2 mRNA levels of the middle and distal intestinal mucosa in AX10 group were also lower than those in Con group. Additionally, the levels of GSH, GST, MDA in the plasma, SOD and CAT in the middle and distal intestinal mucosa, as well as MDA in the middle intestinal mucosa, were significantly higher in AX10 group compared to the CAX and Con groups. Conversely, the levels of CAT, GSH-Px, IGF-1, mTOR, AST in the plasma and AMPD, GDH in the liver were significantly lower in AX10 group compared to the CAX and Con groups. Furthermore, the Chao 1, Shannon index, and the abundance of Cyanobacteria, Aurantimicrobium, Bacteroides decreased with the decreasing dietary AX content. In contrast, the abundance of Proteobacteria, Actinobacteria, and Stenotrophomonas were increased in AX10 group compared to Con group.Discussion and conclusionThese results suggest that high AX (10%) diets may reduce the chemical barrier, antioxidant function, and protein metabolism in rainbow trout, while also reducing intestinal microbiome α-diversity and retarding the colonization of beneficial bacteria.